2019
DOI: 10.1186/s12874-019-0709-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage estimation to adjust for treatment switching in randomised trials: a simulation study investigating the use of inverse probability weighting instead of re-censoring

Abstract: Background Treatment switching is common in randomised trials of oncology treatments, with control group patients switching onto the experimental treatment during follow-up. This distorts an intention-to-treat comparison of the treatments under investigation. Two-stage estimation (TSE) can be used to estimate counterfactual survival times for patients who switch treatments – that is, survival times that would have been observed in the absence of switching. However, when switchers do not die during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Fourth, the results in this paper may not be generalizable to other types of outcomes. Some previous studies compared different methods to address treatment nonadherence when the outcome is continuous [ 60 , 61 ] and time-to-event [ 26 , 62 64 ]. However, these studies mostly focused on comparing either IV or PP methods with the naive methods, or considered different data structures or treatment strategies (e.g., sustained treatment strategies in longitudinal studies) [ 26 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the results in this paper may not be generalizable to other types of outcomes. Some previous studies compared different methods to address treatment nonadherence when the outcome is continuous [ 60 , 61 ] and time-to-event [ 26 , 62 64 ]. However, these studies mostly focused on comparing either IV or PP methods with the naive methods, or considered different data structures or treatment strategies (e.g., sustained treatment strategies in longitudinal studies) [ 26 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies compared different methods to address treatment nonadherence when the outcome is continuous [ 60 , 61 ] and time-to-event [ 26 , 62 64 ]. However, these studies mostly focused on comparing either IV or PP methods with the naive methods, or considered different data structures or treatment strategies (e.g., sustained treatment strategies in longitudinal studies) [ 26 , 64 ]. Future studies should explore the performance of both IV and PP methods in the point-treatment setting for continuous and time-to-event outcomes, multiple treatment arms, and when effect modifiers are present.…”
Section: Discussionmentioning
confidence: 99%
“…In one previous study it was demonstrated that this results in adequate coverage levels, in scenarios where adjustment methods result in low bias. 46 We therefore chose to focus on bias in this study, and are confident that methods that produce low bias would provide adequate standard errors and coverage provided bootstrapping is used.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 This is consistent with previous approaches used to create adjusted counterfactual survival times in cross-over trials. 40 The same procedure was applied to the Cox PH model. The Adjutorium model incorporates four treatments: chemotherapy, hormone therapy, bisphosphonates and trastuzumab.…”
Section: Model Developmentmentioning
confidence: 99%